Novel insights into nanomaterials for immunomodulatory bone regeneration. Issue 2 (22nd December 2021) - Cui, Ya; Li, Hairui; Li, Yaxin; Mao, Lixia
Abstract : Bone defect repair caused by trauma, congenital malformation, tumors, infection or systemic diseases remains the focus of attention in regeneration medicine. Abstract : Bone defect repair caused by trauma, congenital malformation, tumors, infection or systemic diseases remains the focus of attention in regeneration medicine. Recent advances in osteoimmunology indicate that immune cells and correlative cytokines modulate the delicate balance between osteoblasts and osteoclasts and induce a favorable microenvironment for bone regeneration. With superior attributes that imitate the three-dimensional architecture of natural bone, excellent fabricability, mechanical and biological properties, nanomaterials (NMs) are becoming attractive in the field of bone tissue engineering. Particularly, it could be an effective strategy for immunomodulatory bone regeneration by engineering NMs involved in composition nature, nanoarchitectural morphology, surface chemistry, topography and biological molecules, whose mechanisms potentially refer to regulating the phenotype of high-plastic immune cells and inducing cytokine secretion to accelerate osteogenesis. Despite these prominent achievements, the employment of NMs is poorly translated into clinical trials due to the lack of knowledge about the interaction between NMs and the immune system. For this reason, we sketch out the hierarchical structure of bone and its natural healing process, followed by discussion about the effects of immune cells on bone regeneration. Novel horizons focusing on recent progressions in the architectural and physicochemical performances of NMs and their impacts on the body defence mechanism are also emphasized, hoping to provide novel insights for the fabrication of bone graft materials in tissue engineering.